2021
DOI: 10.1186/s13102-021-00326-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered trunk and lower extremity movement coordination after neuromuscular training with and without external focus instruction: a randomized controlled trial

Abstract: Background This study sought to determine the effects of a 6-week neuromuscular training (NMT) and NMT plus external focus (NMT plus EF) programs on trunk and lower extremity inter-segmental movement coordination in active individuals at risk of injury. Methods Forty-six active male athletes (controls = 15, NMT = 16, NMT plus EF = 15) participated (age = 23.26 ± 2.31 years) in this controlled, laboratory study. Three-dimensional kinematics were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…The human body is considered an inter-connected kinetic chain in which compensation movements or defects in one area cause functional defects in other parts of the body [ 49 ]. In fact, the movements of a joint are affected by the adjacent joints and affect them as well [ 50 ]. Biomechanical patterns that increase the DKV, decrease hip, knee, and trunk flexion, excessive trunk lateral flexion, and ankle dorsiflexion limitation increase the risk of ACL injury [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human body is considered an inter-connected kinetic chain in which compensation movements or defects in one area cause functional defects in other parts of the body [ 49 ]. In fact, the movements of a joint are affected by the adjacent joints and affect them as well [ 50 ]. Biomechanical patterns that increase the DKV, decrease hip, knee, and trunk flexion, excessive trunk lateral flexion, and ankle dorsiflexion limitation increase the risk of ACL injury [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have generally demonstrated that adopting an external focus of attention is beneficial for the performance of tasks in different sports such as golf, rowing, and basketball [3][4][5]. Research in the field also explored the effects of attentional focus strategies on movement coordination and landing biomechanics in athletes with anterior cruciate ligament reconstruction [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria included athletes in three sports (handball, volleyball, and basketball), and (a) dynamic knee valgus more than 10 degrees during single-leg landing [ 13 ], (b) no injury to the trunk and lower extremity during the last six months, (c) age 20 to 25 years, and (d) BMI between 18.5–25 kg/m 2 . Exclusion criteria were: musculoskeletal abnormalities, history of fracture or dislocation of the hip, knee and ankle, history of lower back pain in the past year, and inability to perform functional tasks (visual and/or hearing, vestibular, and neurological impairments) [ 25 , 47 ].…”
Section: Methodsmentioning
confidence: 99%